Viral load and its relationship with the inflammatory response and clinical outcomes in hospitalization of patients with COVID-19 - Kuri-Ayache, Mauricio; Rivera-Cavazos, Andrea; Pérez-Castillo, María Fátima; Santos-Macías, Juan Enrique; González-Cantú, Arnulfo; Luviano-García, José Antonio; Jaime-Villalón, Diego; Gutierrez-González, Dalia; Romero-Ibarguengoitia, Maria Elena (Frontiers in Immunology, 2023)
Background The values of viral load in COVID-19 disease have gained relevance, seeking to understand its prognostic value and its behavior in the course of the disease, although there have been no conclusive results. In this study we sought to analyze serum viral load as a predictor of clinical outcome of the disease, as well as its association with inflammatory markers. Methods An observational and retrospective study in a private hospital in North Mexico, patients with SARS-COV-2 infection confirmed by reverse transcriptase polymerase chain reaction (RT-PCR) were followed through clinical outcome, viral load measurement, quantification of inflammatory markers and lymphocyte subpopulations. For the analysis, multiple regression models were performed. Results: We studied 105 patients [47 (SD 1.46) years old, 68.6% men]. After analysis with multiple regression models, there was an association between viral load at admission and vaccination schedule (β-value=-0.279, p= 0.007), age (β-value= 0.010, p = 0.050), mechanical ventilation (β-value= 0.872, p = 0.007), lactate dehydrogenase (β-value= 1.712, p= 0.004), D-dimer values at admission (β-value= 0.847, p= 0.013) and subpopulation of B lymphocytes at admission (β-value= -0.527, p= 0.042). There was no association with days of hospitalization, use of nasal prongs or high flux mask. Peak viral load (10 days after symptoms onset) was associated with peak IL-6 (β-value= 0.470, p= 0.011). Peak viral load matched with peak procalcitonin and minimal lymphocyte values. C-reactive protein peak was before the peak of viral load. The minimum value viral load was documented on day 12 after symptom onset; it matched with the minimum values of IL-6 and ferritin, and the peak of D-dimer. Conclusions SARS-COV-2 admission viral load is associated with vaccination status, mechanical ventilation, and different inflammatory markers.